2020
DOI: 10.1093/ibd/izaa056
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the MARS-5 in Assessing Medication Adherence in IBD

Abstract: Introduction We aimed to validate the Medication Adherence Report Scale-5 (MARS-5) as a tool for assessing medication adherence in inflammatory bowel disease (IBD) and to determine predictors of medication adherence. Methods One hundred twelve (N = 112) adults with confirmed IBD participating in the longitudinal Manitoba Living With IBD Study were eligible. Demographics, IBD type, surgeries, disease activity (using the Inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
5
13
0
Order By: Relevance
“…Several studies have assessed oral medicine adherence in CD patient, 33 , 34 and reported a high non-adherence rate. For example, Kane et al showed that 43%~60% of IBD patients had non-adherence to medication.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed oral medicine adherence in CD patient, 33 , 34 and reported a high non-adherence rate. For example, Kane et al showed that 43%~60% of IBD patients had non-adherence to medication.…”
Section: Discussionmentioning
confidence: 99%
“…The original version of the scale was also validated in English, to study other noncommunicable or chronic diseases, such as stroke, chronic obstructive pulmonary disease, or inflammatory bowel disease [24,25,27].…”
Section: Instrumentmentioning
confidence: 99%
“…The Medication Adherence Report Scale (MARS© Prof. Rob Horne), a self-report questionnaire, originally developed in English, is described as one of the faster instruments to administer to patients, is easier for nurses to assess [24], and it is an appropriate scale to measure medication adherence in patients with non-communicable or chronic diseases [25]. The purposes of the present study were to (i) evaluate the levels of adherence to polypharmacy in spatiotemporally-oriented hospitalized patients, aged 65 years and older, with chronic diseases; and (ii) evaluate the possible association of polypharmacy adherence to the sociodemographic characteristics of the enrolled sample.…”
Section: Introductionmentioning
confidence: 99%
“…The scores calculated by this questionnaire range from 5 to 25, with higher scores indicating a higher degree of medication adherence. A score of 20 points or less, i.e., 80% or below, was defined as low medication adherence [23].…”
Section: Data Collectionmentioning
confidence: 99%
“…To date, few studies have analyzed the factors associated with medication adherence in patients with IBD, especially in an Asian context [13,15,20,21]. It is difficult to apply the results of previous studies on medication adherence that have been conducted in Western patients with IBD [14,17,22,23] or in Korean patients with other chronic diseases [24]. Hence, in our present study we analyzed the factors associated with medication adherence in Korean patients with IBD using a structured questionnaire.…”
mentioning
confidence: 99%